Lack of Latin American women in senior-level positions in Spain-based companies: Barriers to objective career success - Quishpi, J.E. (2022)
Latin Americans are considered one of the largest immigrant groups in the country. However, there is a great unbalance between the number of Latin Americans in the country and the amount of them in the high-skilled labour market. This situation is not different for women, as only 13.8% of them had high-skilled jobs in 2006 (Oso Casas and Martínez, 2008). Women have been particularly overlooked by the literature, with unknown studies covering their presence in the Spanish high-skilled market and in executive positions.